20.9k views
4 votes
Which of the following is equivalent to the expression (9x^2y^3)(12x^-3y^5)(2xy)?

Which of the following is equivalent to the expression (9x^2y^3)(12x^-3y^5)(2xy)?-example-1
User Nnikolay
by
4.5k points

2 Answers

5 votes

Answer:


\large\boxed{(9x^2y^3)(12x^(-3)y^5)(2xy)=216y^9}\to\boxed{B.}

Explanation:


(9x^2y^3)(12x^(-3)y^5)(2xy)=(9\cdot12\cdot2)(x^2x^(-3)x)(y^3y^5y)\\\\\text{Use}\ a^n\cdot a^m=a^(n+m)\\\\=216x^(2+(-3)+1)y^(3+5+1)=216x^0y^9\\\\\text{Use}\ a^0=1\ \text{for any value of}\ a\ \text{except 0}\\\\=216y^9

User AlexHalkin
by
5.1k points
2 votes

Answer:


=216y^9

Explanation:

the expression is:


(9x^2y^3)(12x^(-3)y^5)(2xy)

the first step is to multiply all the coefficients:


9*12*2=216

and as for the variables, to multiply them we must add the exponents, that is, the result for x will be:


x^(2-3+1)=x^0=1

so there will be no x in our result.

adding the exponents for the y variable:


y^(3+5+1)=y^9

The result is the multiplied coefficients and the variables after we add the exponents they in the original expression:


(9x^2y^3)(12x^(-3)y^5)(2xy)
=216y^9

which is option B

User Anilyeni
by
5.7k points